Three-dimensional testicular organoids as novel in vitro models of testicular biology and toxicology. Issue 3 (31st July 2019) - Sakib, Sadman; Voigt, Anna; Goldsmith, Taylor; Dobrinski, Ina
Abstract: Organoids are three dimensional structures consisting of multiple cell types that recapitulate the cellular architecture and functionality of native organs. Over the last decade, the advent of organoid research has opened up many avenues for basic and translational studies. Following suit of other disciplines, research groups working in the field of male reproductive biology have started establishing and characterizing testicular organoids. The three-dimensional architectural and functional similarities of organoids to their tissue of origin facilitate study of complex cell interactions, tissue development and establishment of representative, scalable models for drug and toxicity screening. In this review, we discuss the current state of testicular organoid research, their advantages over conventional monolayer culture and their potential applications in the field of reproductive biology and toxicology.